PENGARUH PENGGUNAAN METODE PEMBELAJARAN ROLE PLAYING TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Maidar, Maidar (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Quality education is highly dependent on the teaching strategies used by teachers to improve student learning outcomes. Role-playing is one approach to increase student engagement in learning. The purpose of this study was to see how the role-playing method affects student learning outcomes in Islamic religious education subjects at SMP Negeri 2 Tapaktuan, South Aceh. This study used quantitative techniques using a pre-test, post-test, control experimental design. This study involved two groups: the experimental group used the role-playing method, and the control group used the usual method. To assess student understanding, the research instrument was a written test with multiple choices and fill-in-the-blank questions. Data collection strategies included giving pre-tests and post-tests to both groups before and after the learning process. The data obtained were analyzed using a t-test for two independent samples. The results showed a significant difference between the experimental group and the control group. The average post-test score of the experimental group was 80.30, while the control group was 72.3, with a t value (2.59) greater than the t table (2.02), indicating that the role-playing approach was more effective in improving student learning outcomes compared to the lecture method. Thus, this study reveals that the use of role-playing strategies can improve students' learning outcomes, especially in terms of social skills and problem solving.